Seasonal variations of subsurface seismic velocities monitored by the SEIS-InSight seismometer on Mars. Issue 2 (15th December 2021) - Compaire, N; Margerin, L; Monnereau, M; Garcia, R F; Lange, L; Calvet, M; Dahmen, N L; Stähler, S C; Mueller, N; Grott, M; Lognonné, P; Spohn, T; et al.
SUMMARY: The SEIS (Seismic Experiment for Interior Structure) seismometer deployed at the surface of Mars in the framework of the NASA-InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission has been continuously recording the ground motion at Elysium Planitia for more than one martian year. In this work, we investigate the seasonal variation of the near-surface properties using both background vibrations and a particular class of high-frequency seismic events. We present measurements of relative velocity changes over one martian year and show that they can be modelled by a thermoelastic response of the Martian regolith. Several families of high-frequency seismic multiplets have been observed at various periods of the martian year. These events exhibit complex, repeatable waveforms with an emergent character and a coda that is likely composed of scattered waves. Taking advantage of these properties, we use coda wave interferometry (CWI) to measure relative traveltime changes as a function of the date of occurrence of the quakes. While in some families a stretching of the coda waveform is clearly observed, in other families we observe either no variation or a clear contraction of the waveform. These various behaviors correspond to different conditions of illumination at the InSight landing site, depending on the season. Measurements of velocity changes from the analysis of background vibrations above 5 Hz are consistent with the results from CWI. We identify a frequency band structure in the power spectral density (PSD) that can be tracked over hundreds of days. This band structure is the equivalent in the frequency domain of an autocorrelogram and can be efficiently used to measure relative traveltime changes as a function of frequency. We explain how the PSD analysis allows us to circumvent the contamination of the measurements by the Lander mode excitation which is inevitable in the time domain. The observed velocity changes can be adequately modelled by the thermoelastic response of the regolith to the time-dependent incident solar flux at the seasonal scale. In particular, the model captures the time delay between the surface temperature variations and the velocity changes in the subsurface. Our observations could serve as a basis for a joint inversion of the seismic and thermal properties in the first 20 m below InSight.